Fodor's Rome - Fisher, Robert I. C., 1955-; Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2008)
A guide to traveling in Rome that includes information on where to stay and eat, what the most popular sites are, how to plan a perfect trip, and how to get to specific destinations.
Includes pullout map.
Includes bibliographical references and index.
Young Adult
Keywords: Rome (Italy) -- Guidebooks; Vatican City -- Guidebooks; Rome (Italy) -- Guidebooks; Vatican City -- Guidebooks